1987
DOI: 10.1007/bf01315107
|View full text |Cite
|
Sign up to set email alerts
|

How effective are Calciphos and Phospal?

Abstract: Abstract. Data from 194 published pot and field experiments were used to calculate the fertilizer effectiveness of two commercially available calcined iron-aluminium rock phosphate fertilizers--Calciphos and PhospaI. A very wide range of effectiveness values (RE) relative to superphosphate have been reported for freshly applied fertilizers ( < 0.1 to 3.0). These differences are primarily not due to differences in citrate soluble P, soil pH, plant species and mean annual rainfall. For both fertilizers most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
(28 reference statements)
1
5
1
2
Order By: Relevance
“…the relation between the yield or the plant uptake and increasing rates of P application for different forms of P fertilizers; (ii) to compare the regression constants of the equation fitted to the response curves; and (iii) to express the results in relation to a standard form of P fertilizer which is water-soluble in order to calculate the Relative Agronomic Effectiveness (RAE) of the tested P fertilizer. Although the factors involved in the RAE of the various P fertilizer forms relating to soil properties have been studied more than a century, it is apparent in the literature on the agronomical evaluation of P fertilizers that it is still an actual agronomic problem since the sets of RAE values of a given P form are often contradictory (Bolland and Gilkes, 1987). Many methodological factors can explain this discrepancy, but it basically indicates this approach doesn't take into account the complexity of the process and the interactions involved between the rate of P application and its effects on agronomic response.…”
Section: Consequently Ss/sf Values [Ss/ Sf = (Riwt)/(r/f)]mentioning
confidence: 99%
“…the relation between the yield or the plant uptake and increasing rates of P application for different forms of P fertilizers; (ii) to compare the regression constants of the equation fitted to the response curves; and (iii) to express the results in relation to a standard form of P fertilizer which is water-soluble in order to calculate the Relative Agronomic Effectiveness (RAE) of the tested P fertilizer. Although the factors involved in the RAE of the various P fertilizer forms relating to soil properties have been studied more than a century, it is apparent in the literature on the agronomical evaluation of P fertilizers that it is still an actual agronomic problem since the sets of RAE values of a given P form are often contradictory (Bolland and Gilkes, 1987). Many methodological factors can explain this discrepancy, but it basically indicates this approach doesn't take into account the complexity of the process and the interactions involved between the rate of P application and its effects on agronomic response.…”
Section: Consequently Ss/sf Values [Ss/ Sf = (Riwt)/(r/f)]mentioning
confidence: 99%
“…It can be concluded from these experimental data that the hypothesis P, = P, used for the P fertilizer evaluation by the standard method without isotopic tracers is not valid. This explains many contradictory conclusions published concerning P fertilizer evaluation using the standard response curve method (Bolland and Gilkes, 1987;Ghosh and Gilkes, 1987;Morel et Fardeau, 1988).…”
Section: Effect Of Soil-p Bioavailability On Phosphorus Uptake From Smentioning
confidence: 98%
“…However, problems of choice have arisen because of the large number of new sources which have appeared on the market (Hammond et al, 1986) and, above all, because of contradictory results published concerning comparative measurements of agronomic efficiency of various P fertilizers in field experiments (Bolland and Gilkes, 1987;Ghosh and Gilkes, 1987;Prince, 1953;Stephen and Condron, 1986). In many cases, the contradictions can be explained either by results obtained on soils where there is no agronomical response or by inadequate methods of fertilizer assessment (Bolland and Gilkes, 1987;Morel and Fardeau, 1988;Palmer et al, 1979). We have recently demonstrated that, when the rate and kind of applied P fertilizer vary, the total amount of P taken up by crops in the presence of P fertilizer can mask differences in the evaluated efficiency of the fertilizers (Morel and Fardeau, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The relative agronomic effectiveness (RAE) of these materials under different soil conditions presented divergent results. Bolland and Gilkes (1987) summarized data from 194 published pot and field experiments done with those two P fertilizers and found that a wide range of RAE values relative to superphosphate were reported for freshly applied fertilizers. Low RAE values were observed in experiments on highly P-responsive soils, whereas high RAE values only occurred for sandy soils in which watersoluble P was rapidly leached.…”
Section: Introductionmentioning
confidence: 95%